1990
DOI: 10.1002/app.1990.070410513
|View full text |Cite
|
Sign up to set email alerts
|

Photodegradation of poly(methyl methacrylate) by monochromatic light: Quantum yield, effect of wavelengths, and light intensity

Abstract: SynopsisPoly( methyl methacrylate) (PMMA) was photolyzed with monochromatic light of wavelengths 260, 280, and 300 nm by the use of the Okazaki large spectrograph. The quantum yield of mainchain scission ( aC8), effects of wavelength, and incident photon intensity on the photodegradation were investigated. It turned out that photodegradation of PMMA took place by the irradiation of 260-300 nm light, but did not by the irradiation at X 2 320 nm. The number of main-chain scission ( N c s ) has a maximum value in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
82
0
3

Year Published

1993
1993
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 118 publications
(90 citation statements)
references
References 7 publications
5
82
0
3
Order By: Relevance
“…The UV treatment may modify the PMMA functional end-groups from −CH 3 to −COOH, 13 which results in the changing of charged states near the PMMA surface. Based on these assumptions, the standard ͑with −CH 3 end groups͒ PMMA and UV-treated ͑with −COOH end groups͒ PMMA monomers were estimated using Gaussian 03 with ab initio calculation.…”
Section: Resultsmentioning
confidence: 99%
“…The UV treatment may modify the PMMA functional end-groups from −CH 3 to −COOH, 13 which results in the changing of charged states near the PMMA surface. Based on these assumptions, the standard ͑with −CH 3 end groups͒ PMMA and UV-treated ͑with −COOH end groups͒ PMMA monomers were estimated using Gaussian 03 with ab initio calculation.…”
Section: Resultsmentioning
confidence: 99%
“…The quantum yield of main chain scission (Φ cs ) [49] is dependent on intrinsic viscosity of PVC before irradiation (η o ), irradiation time (t), incident intensity (I o ), M V,O , concentration (C) and Avogadro's number (A). The Φ cs was calculated using Equation (6):…”
Section: Determination Of the Average Molecular Weight (M V ) By The mentioning
confidence: 99%
“…To date, the PMMA photosensitivity under UV radiation is still not completely understood. Early studies reported that the mechanism of photoinduced refractive index increase in PMMA at 325 nm UV radiation was a consequence of photopolymerization of residual monomers [13,14] while other groups demonstrated that the PMMA photodegradation occurred at wavelengths below 320 nm [15,16]. Our recent investigation reported that the main photosensitive mechanism of PMMA-based mPOF irradiated at 325 nm UV light is a competitive process between photodegradation and photopolymerization [17].…”
Section: Introductionmentioning
confidence: 79%